Jazyková a kulturni různorodost v současné české komerčni reklamě - Mrázková, Kamila (Stylistyka, 2015)
The article deals with linguistic heterogeneity in commercial advertisements addressed to the Czech-speaking majority audience in the Czech Republic. Analyzing examples predominantly from the Czech press and television advertisements, the author shows, among others, which foreign languages are used, how elements of foreign languages are incorporated into the Czech texts and what their functions are. The most frequent foreign language used here is English, followed (perhaps surprisingly) by Italian, which is associated with advertisements for culinary products. For most of the advertisements analyzed, recipients can do without any profound knowledge of the foreign language being used, and in fact, often no knowledge of it is necessary to understand them. The most important function of the foreign language elements or even some longer texts in the advertisements is to index associated stereotypes. Foreign languages point to foreign countries, nations, cultures and their supposed qualities, e.g. German in advertisements on cars produced by German manufactures refers to the tradition of German engineers and evokes concepts such as exactness or reliability. Even in those cases where some knowledge of the given foreign language is necessary to understand the advertisement, the indexical function of this language is important, but in a different manner: it points to the addressee as to an educated person, a citizen of the world, and the like.